Dry eye disease and spondyloarthritis: expanding the spectrum of systemic inflammatory disorders associated with ocular surface disease. Data from the international AIDA Network Spondyloarthritis Registry - Vitale, Antonio; Caggiano, Valeria; Martín-Nares, Eduardo; Di Meglio, Nunzia; Sica, Cristian; Hinojosa-Azaola, Andrea; Perfetti, Maria Orsetta; Pagliara, Alessandra; Guidetti, Giorgia; Fonollosa, Alex; Lopez, Roberta; Sbalchiero, Jessica; et al. (Frontiers in Medicine, 2024)
Objective: Dry eye disease (DED) is a condition associated with a myriad of systemic disorders. According to recent preliminary data, axial spondylarthritis (axial-SpA) could represent a new entity associated with DED. Therefore, the aim of this study was to assess DED in axial SpA patients through quantitative and qualitative specific tests, to investigate the potential association between DED and ocular surface damage in axial-SpA patients, as well as to identify potential variables associated with DED. Methods: 71 patients with axial-SpA fulfilling the Assessment of SpondyloArthritis international Society (ASAS) classification criteria and 19 healthy controls were enrolled. Both patients and controls underwent a complete ocular assessment aimed at evaluating tear film and ocular surface including Schirmer test, break up time (BUT), fluorescein and green lissamine staining. The Ocular Surface Disease Index (OSDI) questionnaire was administered to all patients. Results: DED symptoms were reported in 46 (64.8%) patients and 3 (15.8%) healthy controls (p=0.0004). The Odds Ratio to receive the diagnosis of axial-SpA according to the presence of dry-eye related symptoms was 9.2 (95% C.I. 2.72-42.52, p=0.001). Schirmer test values < 6 mm/5 minutes were observed in 31 (43.7%) axial-SpA patients and in 2 (10.5%) healthy controls (p=0.013); a BUT<5 seconds was observed in 34 (47.9%) axial-SpA patients and in 6 (31.6%) healthy controls. The median OSDI score resulted to be 22.9 (IQR=29.35) among axial-SpA patients and 0.0 (IQR=4.69) among healthy controls (p=0.009). Fluorescein and green lissamine staining of the ocular surface indicated a significantly higher Oxford scale grading in axial-SpA patients than healthy controls. Conclusions: axial-SpA patients often complain of eye dryness, which may be quantified with the self-administered OSDI questionnaire and objectively assessed through the tests commonly used for the diagnosis of DED. Patients suspected of having axial-SpA should routinely be asked about dry eye symptoms and evaluated for potential corneal and conjunctival damage.